Impacting Binational Health through Leadership Development: A Program Evaluation of the Leaders across Borders Program, 2010–2014 - Contreras, Omar A.; Rosales, Cecilia B.; Gonzalez-Fagoaga, Eduardo; Valencia, Celina I.; Rangel, Maria Gudelia (Frontiers in Public Health, 2017)
Background: Workforce and leadership development is imperative for the advancement of public health along the U.S./Mexico border. Leaders Across Borders (LaB) aims to train public health and health care workforce of the border region. The LaB is a six-month intensive leadership development program which offers training in various areas of public health. Program curriculum topics include: leadership, border health epidemiology, health diplomacy, border public policies, and conflict resolution. Methods: This article describes the LaB program evaluation outcomes across four LaB cohort graduates between 2010-2014. LaB graduates received an invitation to participate via email in an online questionnaire. Eighty-five percent (n=34) of evaluation participants indicated an improvement in the level of binationality since participating in the LaB program. Identified themes in the evaluation results included increased binational collaborations and partnerships across multidisciplinary organizations that work towards improving the health status of border communities. Approximately 93% (n=37) of the LaB sample were interested in participating in future binational projects while 80% (n=32) indicated interest in the proposal of other binational initiatives. Participants expressed feelings of gratitude from employers who supported their participation and successful completion of LaB. Discussion: Programs such as LaB are important in providing professional development and education to a health care workforce along the U.S./Mexico border that is dedicated to positively impacting the health outcomes of vulnerable populations residing in this region.